Pre-erythrocytic stage malaria parasites: non-circumsporozoite protein antigens. - Hollingdale, M. R. (World Health Organization, 1990)
A series of non-circumsporozoite proteins found in pre-erythrocytic parasites are being developed as putative vaccine candidates. It is anticipated that these will be useful in addition to, rather than instead of, the CS (circumsporozoite) vaccines. It is likely that a greater understanding of the basic biology of malaria parasite-host relationships will lead to development of improved malarial vaccines.